Progression of retinitis pigmentosa on static perimetry, optical coherence tomography, and fundus autofluorescence - Yuhei Iga; Tomoko Hasegawa; Hanako Ohashi Ikeda; Yoshimichi Hirota; Manabu Miyata; Shogo Numa; Yuki Otsuka; Akitaka Tsujikawa (Scientific Reports, 2023)
Abstract In retinitis pigmentosa (RP), photoreceptor degeneration leads to progressive visual field loss and visual impairment. Several therapeutic trials are ongoing aiming to establish effective treatments. Although functional evaluations are commonly used in clinical trials, residual ellipsoid zone (EZ) measurement on optical coherence tomography has been shown to be more sensitive to detect disease progression. Establishment of sensitive outcome measurement is essential to develop new therapeutic strategies. In the current study, we evaluated the progression rates of the disease in 76 eyes of 76 patients with RP, using the residual EZ length, ring-shaped macular hyperautofluorescent (AF), and visual field. Decrease rates measured by the residual EZ area and by the hyper-AF ring area were strongly positively correlated (P < 0.0001, r = 0.71). The reduction rates of the residual EZ length and hyper-AF ring radius were constant regardless of their baseline measurements. Faster annual reduction rates of the hyper-AF ring area or radius were significantly correlated with faster visual field progression (P = 0.03, r = 0.25 and P = 0.004, r = 0.33, respectively). These findings support the usage of morphological measurements such as EZ or hyper-AF ring measurements as outcome measurement for future clinical trials for RP.